Light beam allocation algorithm for eliminating interference in visible light communications - Duc-Quan Nguyen; Ngoc-Tan Nguyen; Nam-Hoang Nguyen; Spirinmanwat, Keattisak (Proceedings (International Conference on Advanced Technologies for Communications), 2016)
In this paper, we present a model of visible light communication (VLC) systems which exploit light beams for downlink transmission. A calculation method is proposed for light beam configuration (LBC) which guarantees no blind areas in the whole VLC coverage while minimizing the number of light beams. As a major contribution in this paper, a light beam allocation algorithm (LBAA) is proposed which aims to eliminate interferences between inter VLC Access Points (inter-APs) by using information of incoming data queue length and co-channel interference (CCI) conditions to decide which VLC beams are used for transmitting data to appropriate user equipment (UEs). By deploying the proposed algorithm, CCI can be eliminated because noise-effected regions and noise-free regions can be separated. Performance of the novel LBAA is analyzed, evaluated and then compared with that of another light beam allocation method using the Round-Robin algorithm. Performance results show that there are significantly improvements in term of SINR, user throughput and packet delay parameters when deploying the proposed LBAA.